2005
DOI: 10.1002/jcb.20515
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphatases as regulators of skeletal development and metabolism

Abstract: The protein tyrosine kinases (PTK) and the protein tyrosine phosphatases (PTPs) are enzymes which play an integral role in tyrosine phosphorylation-dependent signaling cascades. By catalyzing the phosphorylation and dephosphorylation of cellular proteins, these enzymes direct the steady-state levels of specific phosphoproteins and ultimately dictate the functional state of all cells. The importance of this type of signaling in the skeleton is accepted but poorly understood. The contribution of the PTKs to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 89 publications
0
9
0
2
Order By: Relevance
“…Furthermore, certain forms of PTPs have been shown to be a potential target for bisphosphate in the treatment of bone metastasis from cancer. Deregulation of these pathways has been implicated in cancer development and progression [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, certain forms of PTPs have been shown to be a potential target for bisphosphate in the treatment of bone metastasis from cancer. Deregulation of these pathways has been implicated in cancer development and progression [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prominent, but by no means exclusive, examples include the ability of the non receptor-type phosphatase PTP1B to regulate glucose homeostasis and body mass, which affects signaling downstream of the insulin and leptin receptors, respectively [33][34][35][36][37][38]. The interested reader is referred to several recent reviews in this field [23,25,[39][40][41][42][43][44][45]. Studies such as these, coupled with recent success in pharmacological manipulation of tyrosine kinase activity in treating human disease, have suggested that inhibitors of specific PTPs may also be useful as pharmaceuticals, and have prompted attempts to develop such inhibitors (e.g.…”
mentioning
confidence: 98%
“…The tyrosine phosphorylation of cellular proteins is a critical signaling event in the regulation of all biological processes, including bone formation and resorption 33. The protein tyrosine kinases (PTKs), which catalyze the addition of a phosphate moiety, and the protein tyrosine phosphatases (PTPs), which remove that phosphate, are essential mediators of this type of signaling.…”
mentioning
confidence: 99%